2022
DOI: 10.3390/ijms232315338
|View full text |Cite
|
Sign up to set email alerts
|

Dual CXCR4/IL-10 Gene-Edited Human Amniotic Mesenchymal Stem Cells Exhibit Robust Therapeutic Properties in Chronic Wound Healing

Abstract: Although stem cells have attracted attention as a novel therapeutic solution for tissue regeneration, their minimal efficacy remains controversial. In the present study, we aimed to investigate the enhanced therapeutic property of CXCR4/IL-10 dual angiogenic/anti-inflammatory gene knock-in amniotic mesenchymal stem cells (AMM) in a wound-healing model. Dual CXCR4 and IL-10 genes were inserted into the AMM genome using transcription-activator-like effector nuclease (TALEN). Matrigel tube formation and anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…Our previous study reported an enhanced migration of the intravenously transplanted Cxcr6 bioengineered MSCs in response to the increased level of its cognate ligand CXCL16 at the wound area [ 16 ]. The overexpression of Cxcr4 , a potent angiogenic factor, also enhanced the migration of MSCs and angiogenesis at the injury site via its cognate ligand CXCL12 [ 29 ]. Similarly, CCR2 overexpressed MSCs exhibited increased homing toward the injury site in response to the increased level of CCL2 in diabetic db/db mice wounds [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reported an enhanced migration of the intravenously transplanted Cxcr6 bioengineered MSCs in response to the increased level of its cognate ligand CXCL16 at the wound area [ 16 ]. The overexpression of Cxcr4 , a potent angiogenic factor, also enhanced the migration of MSCs and angiogenesis at the injury site via its cognate ligand CXCL12 [ 29 ]. Similarly, CCR2 overexpressed MSCs exhibited increased homing toward the injury site in response to the increased level of CCL2 in diabetic db/db mice wounds [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressing pro‐survival, proangiogenic, or antiapoptotic genes, such as protein kinase B (Akt1), adrenomedullin, B‐cell lymphoma‐2 (Bcl‐2), and heme oxygenase‐1 (HO‐1), has significantly increased the survival of MSC in vivo 126–128 . Viral alteration has also enhanced MSC migration to areas of damage, inflammation, and malignancy by overexpressing homing receptors such C‐C chemokine receptor type‐1 (CCR‐1) 129,130 and chemokine (C‐X‐C motif) receptor 4 (CXCR4) 131,132 . In the myocardium's injured infarct area, more MSC than normal MSC overexpress CXCR4 home.…”
Section: The Rationally Of Mscs Engineeringmentioning
confidence: 99%
“…Investigations have shown that cells release some growth factors 15,16 and cytokines, 17,18 such as epithelial growth factor, fibroblast growth factor, transforming growth factor, keratinocyte growth factor, IL‐6, and IL‐10. These mediators promote cellular proliferation, migration, and differentiation and reduce tissue inflammation and infection 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…These mediators promote cellular proliferation, migration, and differentiation and reduce tissue inflammation and infection. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation